Bc-cx=-c

Simple and best practice solution for Bc-cx=-c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Bc-cx=-c equation:


Simplifying
Bc + -1cx = -1c

Solving
cB + -1cx = -1c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add 'c' to each side of the equation.
cB + c + -1cx = -1c + c

Reorder the terms:
c + cB + -1cx = -1c + c

Combine like terms: -1c + c = 0
c + cB + -1cx = 0

Factor out the Greatest Common Factor (GCF), 'c'.
c(1 + B + -1x) = 0

Subproblem 1

Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0

Subproblem 2

Set the factor '(1 + B + -1x)' equal to zero and attempt to solve: Simplifying 1 + B + -1x = 0 Solving 1 + B + -1x = 0 Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + B + -1 + -1x = 0 + -1 Reorder the terms: 1 + -1 + B + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + B + -1x = 0 + -1 B + -1x = 0 + -1 Combine like terms: 0 + -1 = -1 B + -1x = -1 Add '-1B' to each side of the equation. B + -1B + -1x = -1 + -1B Combine like terms: B + -1B = 0 0 + -1x = -1 + -1B -1x = -1 + -1B Add 'x' to each side of the equation. -1x + x = -1 + -1B + x Combine like terms: -1x + x = 0 0 = -1 + -1B + x Simplifying 0 = -1 + -1B + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

c = {0}

See similar equations:

| -30=1.5c | | 8*10=3*2 | | 8w-2=7w+73 | | 14+22+5x-2x=27 | | 4*5(x-3)+2*(x-5)= | | 12n+81=108+12n | | -54a^4b^3+9a^3b^4=27a^4b^4 | | 54=-9 | | (5x-13)-(6-5x)=7 | | 542=-9 | | 6m-2[7+m]=4m-10 | | 8x+5-3(x+1)=9x+5 | | X(3x-1)(x+1)-(5x-1)(x-1)= | | 24a-2=4 | | 4n-7=3n+15 | | 6x+8=5x+7 | | 6x^7-4x^2+10x= | | 4x-30=6(x+2) | | 4-3(2y-8)-3y= | | 6(x-6)-5(x-1)=2(x+3) | | 3x+9=3x-15 | | 8x+90= | | 3v+12=30 | | 6b-[2b+16]=-24 | | 4[7x+2]-8=-7 | | f(4+1)=-2f(4) | | 2v-8=18 | | -4(x+1)-x-9=-5(x+4)+7 | | 24y^7+3y^2= | | 60f+55=119f+126+12f | | (3x-1)(4-2x)(5x+9)=0 | | -3b+8[b+2]=-19 |

Equations solver categories